Muslims in British local government : representing minority interests in Jackney, Newham, and Tower Hamlets - Tatari, Eren. (Muslim Minorities, 2014)
This book investigates whether the presence of Muslim representatives in city councils improves substantive representation of Muslim interests across 32 London boroughs. It theorizes that descriptive representation of minorities leads to improved responsiveness to minority interests contingent on the percentage of minority representatives, the proportion of minorities in the district, level of party fragmentation among minority representatives, their political incorporation, and the electoral competitiveness of the district. It uses multivariate regression analysis to test the effects of these five explanatory variables. It validates the quantitative findings with case studies of three London boroughs while also investigating the role of representational styles of Muslim councillors on their political attitudes and behavior.